The Effect of Social Support on Elementary School Students' Self-Efficacy and Academic Burnout: A MANOVA Approach - Rahmawati, Aulia Dwi; Deviani, Anin; Tujduja, Muniro (CV. Akademi Merdeka, 2024)
This study investigates the influence of social support comprising parental, teacher, and peer support on elementary school students’ self-efficacy and academic burnout. Utilizing a quantitative approach with a causal-comparative design, data were collected from 240 fifth and sixth-grade students in Cirebon, Indonesia. The research employed Multivariate Analysis of Variance (MANOVA) to analyze the simultaneous impact of support on two dependent variables: self-efficacy and burnout. The findings indicate that while levels of social support did not significantly affect students’ self-efficacy, they had a statistically significant impact on academic burnout. Higher levels of support were associated with lower levels of academic burnout. These results highlight the essential role of a supportive environment in mitigating emotional exhaustion among young learners. The study underscores the importance of strengthening school-based and family-based support systems to promote students' psychological well-being and prevent early academic disengagement.